Application of a Literacy Culture Approach to Foster Student Learning Motivation - Hidayatul Ummah; Budi Hariyanto; Taufiq Churrohman (International Consortium of Education and Culture Research Studies, 2020)
Literacy culture is a habit practiced by every individual to use their abilities and potentials. Literacy is applied in schools / madrasas before the learning time starts getting used to students to read non-textbooks. The purpose of this research is to increase students' motivation to learn from habits that are built early on. This research is a type of qualitative research with observational methods, interviews and documentation from various data sources, which will be the respondents to be interviewed are the headmaster of Muhammadiyah 3 Waru Middle School, some teaching teachers and some of the junior high school students in the school. The results of this study are 1) the existence of literacy culture is able to increase student motivation, in SMP Muhammadiyah 3 Waru with a culture of reading before the lesson starts approximately 15 minutes, 2) there are supporting and inhibiting factors in implementing this literacy culture as for supporting factors from the literacy culture in the school with adequate facilities and infrastructure and the absence of students who arrive late for school to take part in literacy program activities. Lack of motivation from students themselves or outside students, so the lack of supporting facilities and infrastructure. 3) solving the existing problems is increasing the motivation of various parties, especially the school and parents of students as well as supporting facilities and infrastructure.